2012
DOI: 10.1021/bi3009104
|View full text |Cite
|
Sign up to set email alerts
|

Transient Kinetic Analysis of USP2-Catalyzed Deubiquitination Reveals a Conformational Rearrangement in the K48-Linked Diubiquitin Substrate

Abstract: Deubiquitination has emerged as an essential regulatory mechanism of a number of cellular processes. An in-depth understanding of deubiquitinating enzyme (DUB) catalysis, particularly the mode of ubiquitin binding and the individual steps in the DUB catalytic turnover, is imperative for exploiting DUBs for therapeutic intervention. In this work we present a transient kinetic study of USP2 in hydrolyzing a model substrate Ub-AMC and a physiological substrate K48-linked diubiquitin. We carried out stopped-flow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
19
2
Order By: Relevance
“…ZnKO USP2CD displayed reduced enzymatic activity as a result of increased K m from 1.8 µM to 26 µM (Figure 4B and C) whereas k cat was increased by only 2-fold (0.55 to 1.3 s −1 ). It has been previously determined that for USP2CD K m is comparable to K d 40 . Our measurement suggested a reduction in ZnKO USP2CD’s Ub binding capacity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…ZnKO USP2CD displayed reduced enzymatic activity as a result of increased K m from 1.8 µM to 26 µM (Figure 4B and C) whereas k cat was increased by only 2-fold (0.55 to 1.3 s −1 ). It has been previously determined that for USP2CD K m is comparable to K d 40 . Our measurement suggested a reduction in ZnKO USP2CD’s Ub binding capacity.…”
Section: Resultsmentioning
confidence: 96%
“…Human USP2 catalytic domain (USP2CD, amino acids 259—605), USP7 catalytic domain (USP7CD, amino acids 208—564) and USP7 catalytic domain with Ub-like domains 4 and 5 (USP7CD45, amino acids 208—564 and 890—1102 with a Leu and Glu linker) was cloned into pET-28a vector based on constructs previously reported except that the GST tag was not included in our construct 16,40 . USP8 catalytic domain (USP8CD, amino acids 734—1110) in pET-28a was generously donated by Dr. Sirano Dhe-Pagano 20 .…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, Shan et al (4) reported that the knockdown of USP2 arrests cancer cell growth by promoting the proteasome-mediated degradation of cyclin D1, thus raising the possibility that small molecules specifically targeting this deubiquitinase could be effective chemotherapeutic agents for cancers addicted to cyclin D1 expression. A crystal structure of USP2 and kinetic analysis of its interaction with ubiquitin have been reported (16,17); however, only a few USP2 inhibitors have been described, and several of these bind covalently and/or are nonselective (18 -20). Herein, we report the identification of a small molecule USP2 inhibitor, ML364, demonstrate its activity in USP2 biochemical assays, and profile its selectivity across a panel of proteases and kinases.…”
mentioning
confidence: 99%
“…5a). DUB dosage-response data [10] did show a monotonic action of DUB, in which higher DUB concentration renders greater discrimination against CD4-M. We note, in this regime, the DUB rate is higher than reported kcat = 0.35 s −1 [22] and kcat = 0.53 s −1 [23] for UPS2-CD used in Ref. [10].…”
Section: Resultsmentioning
confidence: 60%